Role of Phloroglucinol in Reducing Duration of Active 1st Stage of Labour (Medical Forum Monthly, 2024)
Objective: To make a comparison between the mean duration of active 1st stage of labour with phloroglucinol versus placebo.Study Design: Randomized controlled trial studyPlace and Duration of Study: This study was conducted at the Department of Gynae and Obs., Lady Aitcheson Hospital Lahore from 1st July 2017 31st December 2017.Materials and Methods: A total of 60 cases with singleton pregnancy ,in active 1st stage of uncomplicated labour and between 18 to 40 years of age were included. Patients with multiple pregnancy, history of obstetrical, surgical and medical complications were excluded. The patients fulfilling inclusion criteria were placed randomly into two groups i.e. Group A (phloroglucinol) and Group B (placebo), by using lottery method. After this, duration of the 1st stage of labour was noted in minutes.Results: The mean age of patients in group A was 27.27±5.26 years and in group B was 26.87±5.44 years. The mean gestational age in group A was 38.37±1.40 weeks and in group B was 38.57±1.38 weeks. Mean duration of 1st stage of labour in Group A was 230.20 ± 52.96 minutes while in Group B was 345.30±50.57 minutes (p-value<0.0001).Conclusion: It was inferred that phloroglucinol has an important role in making duration of active 1st stage of labour short.